SAT0146 Randomised double-blind study shows comparable long-term efficacy and safety between rituximab biosimilar CT-P10 and innovator rituximab in patients with rheumatoid arthritis: 48-week results. (15th June 2017) - Suh, C-H; Khouri, E Chalouhi El; Miranda, P; Molina, F F Cons; Shesternya, P; Medina-Rodriguez, F; Wiland, P; Jeka, S; Chavez-Corrales, J; Linde, T; Hrycaj, P; Hospodarskyy, I; et al.
Abstract : Background: In phase 1 trials (NCT01534884 and NCT01873443 ), pharmacokinetic equivalence of CT-P10, biosimilar of rituximab, to innovator rituximab (RTX) was demonstrated. In the phase 3 study, equivalence of PK and efficacy up to week 24 were achieved between CT-P10 and RTX (US and EU sourced) 1, 2 . Objectives: To investigate the long-term efficacy, pharmacodynamics, immunogenicity and safety of CT-P10 up to week 48. Methods: Patients with rheumatoid arthritis were randomly assigned to CT-P10, US-RTX or EU-RTX, in combination with MTX. The patients received 2 treatment courses at Week 0 and 24, each consisting of 2 infusions of 1000mg study drug at 2-week interval. Results: A total of 372 patients were randomised, and 330 patients completed the 2nd course treatment. DAS28 scores through Week 48 were comparable between CT-P10 and US/EU-RTX (Figure), as well as the proportion of ACR responses at Week 48 between the CT-P10 and combined rituximab groups; 81.3% and 79.8% for ACR 20, 55.4% and 53.9% for ACR50, and 31.7% and 33.7% for ACR 70, respectively. B-cell depletion was comparable from after the 1st infusion and up to Week 48. Number (%) of patients with positive anti-drug antibodies in the CT-P10, US-RTX, and EU-RTX was 7 (4.9), 13 (9.4), and 5 (8.6), respectively at Week 48. The safety profile was also similar across groups (Table). Conclusions: This phase 3 randomised controlled trial demonstrated the comparability of CT-P10 with two rituximab in terms of efficacy, pharmacodynamics, immunogenicity and safety for 1 year. References: Suh CH, et al. 2016 ACR Abstract No. 1634. Yoo DH, et al. 2016 ACR Abstract No. 1635. Disclosure of Interest: C.-H. Suh Consultant for: Celltrion, Inc., E. Chalouhi El Khouri Grant/research support from: Celltrion, Inc., P. Miranda Grant/research support from: Celltrion, Inc., F. F Cons Molina Grant/research support from: Celltrion, Inc., P. Shesternya Grant/research support from: Celltrion, Inc., F. Medina-Rodriguez Grant/research support from: Celltrion, Inc., P. Wiland Grant/research support from: Celltrion, Inc., S. Jeka Grant/research support from: Celltrion, Inc., J. Chavez-Corrales Grant/research support from: Celltrion, Inc., T. Linde Grant/research support from: Celltrion, Inc., P. Hrycaj Grant/research support from: Celltrion, Inc., I. Hospodarskyy Grant/research support from: Celltrion, Inc., M. Abello-Banfi Grant/research support from: Celltrion, Inc., J. Jaworski Grant/research support from: Celltrion, Inc., M. Piotrowski Grant/research support from: Celltrion, Inc., W. Park Consultant for: Celltrion, Inc., S. C. Shim Consultant for: Celltrion, Inc., S. J. Lee Employee of: Celltrion, Inc., S. Y. Lee Employee of: Celltrion, Inc., D. H. Yoo Consultant for: Celltrion, Inc.